Tumour-suppressive miRNA-26a-5p and miR-26b-5p inhibit cell aggressiveness by regulating PLOD2 in bladder cancer - Miyamoto, K (Br J Cancer, 2016)
BACKGROUND: Previous studies have revealed that miR-26a-5p and miR-26b-5p act as tumour suppressors in various types of cancer tissues. Here, we aimed to investigate the functional roles of these miRNAs and to identify their regulatory targets in bladder cancer (BC). METHODS: We performed functional assays in BC cells using transfection of mature microRNAs (miRNAs). In silico and luciferase reporter analyses were applied to identify target genes of these miRNAs. The overall survival (OS) of patients with BC was evaluated by the Kaplan–Meier method. RESULTS: miR-26a-5p and miR-26b-5p were significantly downregulated in BC tissues. Restoration of these miRNAs inhibited cell migration and invasion in BC. The gene encoding procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 (PLOD2), a collagen crosslinking enzyme, was directly regulated by miR-26a-5p and miR-26b-5p. Kaplan–Meier analysis revealed that patients with high PLOD2 expression had significantly shorter OS compared with those with low PLOD2 expression (P=0.0153). CONCLUSIONS: PLOD2, which is associated with the stiffness of the extracellular matrix, was directly regulated by miR-26a-5p and miR-26b-5p and may be a good prognostic marker in patients with BC.